Digital HRM Capability, HPWS and Service Performance: The Mediating Role of Employee Engagement at PT PELNI, Indonesia - Suharno Pawirosumarto; Syamsyir Luchan; Elfiswandi Elfiswandi (Dinasti International Journal of Education Management and Social Science, 2026)
This study examines how Digital HRM capability and high-performance work systems (HPWS) influence employee service performance through employee engagement in Indonesia’s state-owned maritime transport context (PT PELNI). A cross-sectional survey of Head Office employees was analysed using PLS-SEM; reliability and validity were assessed, and mediation was tested via bootstrapped indirect effects (5,000 resamples). Digital HRM capability is positively associated with employee engagement, and engagement is strongly associated with employee-level service performance. Engagement mediates the relationship between Digital HRM capability and service performance (indirect-only mediation), indicating that digital HR capability contributes to service outcomes primarily by shaping employee experience. In contrast, HPWS is not significantly related to engagement, and the hypothesised engagement-mediated pathway from HPWS to service performance is not supported. The study contributes by clarifying an employee-experience mechanism linking digital HR capability to service behaviour and extending evidence to an under-researched state-owned maritime service organisation in an emerging-economy context. Keywords: Digital HRM capability; high-performance work systems (HPWS); employee engagement; employee experience; service performance; state-owned enterprise; emerging economy. Article classification: Research paper.